The impact of income-generating strategies at newspapers: a study of Geld - Ueckermann, Helen (My University, 2006)
Newspapers are operating in a changing media environment where commercial pressures have in some cases diluted the information, education and publicity functions of traditional journalism. This research report looks at strategies to attract advertising at publications and the impact of these strategies on journalistic operating approaches, media organisation and culture as well as certain aspects of content, with specific reference to the personal finance magazine Geld, which is published as part of the Afrikaans Sunday newspaper Rapport. The research question is framed in the context of a concern in media studies and the South African media publishing environment about increasing commercialisation and its effect on the role of journalism in society. I employed the research methods of content analysis, quantitative and qualitative, and in-depth interviews to explore the subject.
0302222N, Helen Ueckermann Research report for Masters degree.2005
Keywords: Geld; income; newspapers; Fanus Gous; Rapport